La gestión de tesorería y su relación con los pagos a proveedores de la unidad ejecutora de Ucayali - Contamana, año 2023 - Chuyo Mafaldo, Gelly Leslie (2023)
The objective of this research was to determine the relationship between treasury management and payments to suppliers of the Executive Unit of Ucayali-Contamana, year 2023. The research methodology comprised a basic type, correlational and non-experimental design, quantitative approach, probabilistic sampling, as well as a population and sample of 50 and 45, respectively, among workers linked to treasury management functions in the Ucayali-Contamana Executing Unit, as well as people linked to the process of providing goods and services to the entity (suppliers). The main results demonstrated the importance of treasury management in the Ucayali-Contamana Executing Unit being carried out according to a series of principles, the implementation of financial control and the development of effective collection and payment management, as a basis for compliance with payments to the entity's suppliers. Finally, the main conclusion was to determine that there is a significant relationship between treasury management and payments to suppliers of the Ucayali-Contamana Executing Unit, year 2023. This premise is consistent with the Spearman correlation index 0.828 for the case of the general hypothesis.